ABUNDANCE OF DIATOM AT THE GUMILAMO AND MAGALIHO ISLAND, NORTH HALMAHERA - Rina Puji Astuti; Philip Teguh Imanto; Gede S. Sumiarsa (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
Observation on abundance of diatom has been conducted in Gumilamo-Magaliho waters, North Halmahera. The aims of this study were to identify and analyze daily fluctuations of diatom abundance also analyze the biological indices in the plankton in that waters and . Sampling was conducted at three stations representing the strait, mangrove areas and estuary. Plankton were collected using a plankton net no.25. Sampling was carried out for 24 hours with six hour interval. Identification and counting of cells using a microscope with 400x magnification. The results showed that seven genera of diatoms were found: Chaetoceros sp. with the highest of cells abundance (5.061 cells/L), successively followed by Nitzschia sp. (611 cells/L), Thalassionema sp. (569 cells/L), Skeletonema sp. (446 cells/L), Coscinodiscus sp. (176 cells/L), Navicula sp. (40 cells/L) and Amphora sp. (11 cells/L). At station I and II showed that the maximum abundance occurred at 6 am, and the minimum abundance occurred at 6 pm. At station III the maximum abundance occurred at midnight and a minimum abundance occurred at noon. Diatoms showed different daily fluctuations at different time and stations. The supporting diversity index value of medium, low uniformity, and no dominance factor causing the Gumilamo-Magaliho waters can be developed for aquaculture.Keywords: diatom, diatom abundance